Recurrent dream themes: frequency, emotional tone, and associated factors - Schredl, Michael; Germann, Luca; Rauthmann, John (Dreaming, 2022)
The majority of adults (50% to 75%) report that they have had at least once recurring dreams in their lives; most of these recurrent dreams, for example, being chased, are negatively toned. However, systematic research regarding the content of these dreams is relatively scarce. Within the present online survey, 676 participants (545 women, 131 men) with mean age of 27.26 ± 9.12 years reported a recurrent dream. About two thirds of the dream reports were negatively toned, with the most frequent topics being “failure or helplessness” and “being chased.” Persons with high neuroticism scores were more likely to report a negatively toned recurrent dream. About a quarter of the dreams were positively toned, for example, “romantic and sexual interactions,” “experiencing something pleasant,” or “positive social interactions.” Overall, recurrent dreams seem to reflect waking life, that is, negative waking-life experiences are reflected in negatively toned recurrent dreams. It would be very interesting to study whether strategies such as imagery rehearsal therapy that aim to change dream content are reducing negative recurrent dreams and their negative effects on well-being. (PsycInfo Database Record (c) 2022 APA, all rights reserved)